PENGARUH NISBAH BAGI HASIL, BI RATE DAN INFLASI TERHADAP PEMBIAYAAN MUSYARAKAH PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2010-2021 - , Rahmat Richard, Rezza Ria Ramadhani , Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this study was to determine the influence of the Profit Sharing Ratio, BI Rate, and Inflation on Musyarakah  Financing at Islamic Commercial Banks in Indonesia in 2010-2021. The type of data used is quantitative data. The data source used is secondary data using multiple linear regression analysis with the simple least squares method (Ordinary Least Square/OLS). The results of the study show that the profit sharing ratio has an effect on musyarakah  financing, while the BI Rate and Inflation have no effect on musyarakah  financing at Islamic Commercial Banks in Indonesia in 2010-2021 Keywords: Profit Sharing Ratio, BI Rate, Inflation, Musyarakah  Financing